Finitud y resistencia en La novela luminosa de Mario Levrero - Rosales Rodríguez, Amán (Studia Romanica Posnaniensia, 2024)
In La novela luminosa (2005), the last great narrative project of Uruguayan Mario Levrero, an ambivalent relationship with the space of the everyday is exposed. Everyday life appears, in the first place, as a disturbing dimension that reminds the protagonist of his finitude, that is, his precarious state, both economically and in terms of physical-psychic health. Secondly, however, it is these same unstable conditions of the everyday that also stimulate the feeling of ‘heroic’ resistance exhibited by the protagonist of the autofictional text. La novela luminosa thus pays an ambiguous homage – of acceptance and rejection at the same time – to a daily routine to which its author, on the threshold of old age and close to death, ends up clinging, in spite of everything and until the end, in order to leave testimony of his life as an author by means of a writing that ironizes his own status as a fragmented work.